Le patronat devant le syndicalisme (Relations industrielles / Industrial Relations, 1952)
The article reviews "Le patronat devant le syndicalisme," summayr of the 12th congress of the Fédération des Patrons catholiques de Belgique, held on 15-16 December 1951, published in the Bulletin social des Industriels, January 1952.